Hydrothermal biochar enhances the photosynthetic efficiency and yield of alfalfa by optimizing soil chemical properties and stimulating the activity of microbial communities - Xingquan Yan; Zhijun Wang; Muqier Zhao; Junfeng Hao; Jingyi Liu; Yuting Yan; Pengbo Sun; Yushan Jia; Gentu Ge (Scientific Reports)
Abstract Hydrothermal biochar has demonstrated potential in enhancing crop growth by improving soil properties and microbial activity; however, its effectiveness varies with application rate, with excessive amounts potentially inhibiting plant growth. This study employed a pot experiment approach to compare varying application rates of hydrothermal biochar (ranging from 0 to 50 t/ha) and to analyze its effects on alfalfa biomass, photosynthetic efficiency, soil nutrient content, and microbial community composition. Biochar application increased alfalfa dry weight by 12.22-21.20% in leaves, 31.60-55.60% in stalks, and 5.62-38.05% in roots. It also enhanced the light utilization efficiency of photosystem II. However, excessive biochar (50 t/ha) reduced biomass and photosynthesis. The addition of biochar amendments enhances soil nutrient availability, particularly increasing the accessibility of carbon, nitrogen, and phosphorus, while also lowering soil pH and enriching microbial interactions within bacterial communities. However, the effects on fungal communities are not pronounced. In conclusion, a moderate application of biochar (10-20t/ha) is recommended to maximize the growth of alfalfa and improve soil health, offering a practical approach for the sustainable cultivation of alfalfa.